Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa dalam Pembelajaran PKN Melalui Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI): Efforts to Improve Student Activities and Learning Outcomes in PKN Learning Through Cooperative Learning Type of Team Assisted Individual Ization (TAI) - Junaidi, Junaidi (Anterior Jurnal, 2022)
This study aims to improve student activities and learning outcomes in Civic Education learning by applying the Team Assisted Individualization type of cooperative learning method. This research is classroom action research (CAR), which is reflective research by taking various actions to improve and enhance the learning process in the classroom. Data collection methods used in this study were observation, tests, and documentation. To analyze the data from the results of the activity observation sheet and the class average value using descriptive statistics. The results of the study show that learning Citizenship Education using the TAI type cooperative method can improve student activities and learning outcomes.